(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2023)
During recent excavations for the construction of a methane pipeline in the territory of the municipality of Melzo, north-east of Milan, a small Roman structure was discovered. It probably had functional use and was part of a larger rural settlement, not identified by archaeological investigations. The discovery constitutes new evidence of Roman rural construction in the territory of ancient Mediolanum.